Morphological and simple sequence repeat (SSR)-based diversity of Capsicum germplasm characterizes population structure and enables marker-assisted selection for Phytophthora capsici resistance - Deepa Jaganathan; Jessica Michelle Gibbs; Noel Thomas; Theodore McAvoy; Mahnaz Azad; Miaoying Tian; Dennis N. Lozada; William Hendricks Railey; Amol N. Nankar (Euphytica, 2026)
Capsicum annuum is a globally important crop with rich genetic diversity that underpins breeding for productivity and disease resistance. In this study, we assessed 485 accessions representing a diverse Capsicum germplasm set, predominantly Capsicum annuum with a limited representation of related wild species using agro-morphological traits and simple sequence repeat markers to explore diversity, structure, and trait variation. Phenotypic evaluation of 352 accessions was conducted under field conditions during the 2024 summer season, where data were recorded on eight quantitative and four qualitative traits. Genetic characterization on the whole collection was performed using 24 polymorphic SSR markers selected for their known linkage to Phytophthora capsici resistance. A total of 308 alleles were detected post-binning, with an average of 12.83 alleles per locus and high polymorphism information content (mean PIC = 0.80). STRUCTURE analysis revealed three major genetic clusters (K = 3), supported by the Evanno ΔK method and consistent with clustering observed in Principal Component Analysis (PCA) and Neighbor-Joining (NJ). The clusters comprised predominantly C. annuum accessions, but also included individuals from C. baccatum , C. chinense , and other species, suggesting historical introgression and admixture. Phenotypic variation largely aligned with molecular groupings, supporting the complementary use of morphological and marker-based data. The high allelic diversity and defined population structure observed in this study provide a valuable foundation for genetic improvement, association mapping, and core collection development in Capsicum . In addition, the choice of Phytophthora -linked SSR markers provides an important platform for future association mapping and marker-assisted selection studies aimed at improving disease resistance in Capsicum . Graphical Abstract